The effects of the enhanced social and emotional learning intervention on knowledge, learning anxiety and dropout intention - Deli, Wu (2021)
In view of the widespread prevalence of adolescent psychological health problems and its adverse impact on student academic functioning, social emotional learning (SEL) intervention has become an important pedagogical approach. The purpose of this study was to explore the effectiveness of two kinds of SEL interventions administered by two different types of teachers to determine their effectiveness on the gain in SEL knowledge, learning anxiety and intention to drop out of school. This study adopted a 2 × 2 quasi-factorial design,in which the intervention type and the teacher type were manipulated to produce four different versions of the experiment. A total of 209 Grade 8 students (107 boys and 102 girls) with a mean age of 14.3 years from Qinzhou, Southwest China, participated in the study. The MANOVA data analysis found significant main effect of teacher type, intervention type and interaction of teacher type and intervention type on the combination of SEL knowledge, learning anxiety and dropout intention. We also conducted follow-up ANOVA to identify the interaction on each dependent variable. For SEL knowledge, psychology teacher with teacher autonomy supportive social and emotional learning intervention group was the best intervention group(PT+TASSEL) to improve students’ SEL knowledge. For learning anxiety, psychology teacher with social and emotional learning intervention group was the best intervention group (PT+SEL) to reduce learning anxiety, but teacher autonomy support did not help to reduce learning anxiety, as autonomy gave Chinese students more psychological burden in the collectivism culture. For dropout intention, psychology teacher with teacher autonomy supportive social and emotional learning intervention group was the best intervention group(PT+TASSEL) to reduce dropout intention. The current study developed TASSEL intervention for future researches in China and gave suggestions on how to combine teacher type and intervention type to improve SEL knowledge, reduce learning anxiety and dropout intention.